2018
DOI: 10.1590/1414-431x20187439
|View full text |Cite|
|
Sign up to set email alerts
|

Gastrodin induced HO-1 and Nrf2 up-regulation to alleviate H2O2-induced oxidative stress in mouse liver sinusoidal endothelial cells through p38 MAPK phosphorylation

Abstract: Nuclear factor erythroid-related factor 2 (Nrf2) has been implicated in several detoxifying and antioxidant defense processes. Nrf2-mediated heme oxygenase-1 (HO-1) expression was demonstrated to play a key role against oxidative stress. Gastrodin (GSTD) is a well-known active compound isolated from the roots of Rhizoma gastrodiae, a plant used in ancient Chinese traditional medicine. The aim of this work was to investigate whether GSTD could alleviate H2O2-induced oxidative stress in mouse liver sinusoidal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 39 publications
2
36
1
Order By: Relevance
“…In in vitro experiments, we studied the effect of probucol on MSCs under oxidative stress. The secondary injury following H 2 O 2 represents consecutive pathological processes including oxidative stress and apoptosis [24]. Oxidants and their dericatives generated by H 2 O 2 enhance the generation of ROS and exhaust antioxidant defense enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro experiments, we studied the effect of probucol on MSCs under oxidative stress. The secondary injury following H 2 O 2 represents consecutive pathological processes including oxidative stress and apoptosis [24]. Oxidants and their dericatives generated by H 2 O 2 enhance the generation of ROS and exhaust antioxidant defense enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…39) GSH depletion activates lipoxygenase, inhibits GPX4 activity and triggers lipid peroxidation. 40) Our results show that gastrodin increased the level of GSH and the activity of GPX. Further, the oxidation of endogenous lipids was determined by measuring MDA in C6 cells treated with gastrodin or H 2 O 2 .…”
Section: Discussionsupporting
confidence: 50%
“…This phenomenon may be due partly to the insufficient activation of the Nrf2 /HO-1 pathway to prevent toxicity under TBHP stimulation. It has been reported that GAS can ameliorate oxidative stress-induced damage through the Nrf2 /HO-1 pathway in particular cell types (Zhang et al, 2018). Indeed, the results of our study demonstrated that GAS significantly increased Nrf2 accumulation in the nucleus and HO-1 expression in TBHP-treated HUVECs.…”
Section: Discussionmentioning
confidence: 99%